New forms: Anthropocene Festivals and experimental environmental governance. (March 2022) - Ritts, Max; Bakker, Karen
This paper is about the "Anthropocene Festival, " a concept we develop to explore proliferating and multi-faceted arts-based events, happenings, unconferences, and workshops which collectively model novel forms of environmental governance. The Anthropocene Festival mobilizes disruptive and creative possibilities at the juncture of digital and ecological life, while simultaneously embodying developments in the institutional form of green capitalism. To argue these points, we locate the Anthropocene Festival within a proliferation of new institutional environmentalisms, including biennales, hackathons, and initiatives in the neoliberal university. Next, we provide a survey of recent examples, observing across them an increasingly hegemonic template of environmental sociality—or model of collective interaction—rooted in digital technologies. Next, we discuss two examples of environmental governance propositions expressive of the Anthropocene Festival ethos: (1) Climate Symphony, a project that uses sonification techniques to facilitate new understandings of climate change, (2) Terra0, an art project which reconceptualizes forest ecology and non-human agency using blockchain technology. We conclude by arguing that the ontological generativity of the Anthropocene Festival arises from the dissenting approaches to conventional models of environmental governance it cultivates, but that the Anthropocene Festival does not necessarily carry a radical political valence because of this.